Challenges and Opportunities in Managing Large-Scale Infrastructure Projects: The Case of Indonesia"™s New Capital Nusantara - Pramesti, Nectaria Putri; Basuki, Imam (Jurnal Teknik Sipil, 2025)
The relocation of Indonesia"™s capital to Nusantara (IKN) represents a transformational initiative to establish an innovative, sustainable, and inclusive government center in East Kalimantan. Under a Public-Private Partnership (PPP) model, IKN is envisioned as a carbon-neutral city with resilient infrastructure and technology-based public services. Despite 97,2% completion of the first development phase by early 2025, the project faces significant challenges, including heavy reliance on state funding (85%), limited private sector participation (10%), underdeveloped logistics, and a shortage of skilled labor in technologies such as Building Information Modeling (BIM), Internet of Things (IoT), and modular construction. This study employs a qualitative exploratory approach using secondary data, integrating SWOT analysis, international benchmarking (BrasÃlia, Naypyidaw, Putrajaya), and technological evaluation. Findings indicate that digital construction technologies can improve project efficiency by up to 30% and reduce material waste by 25%. Alternative financing strategies, including green bonds and Islamic crowdfunding, can potentially increase private investment up to 40% by 2030. For long-term success, IKN must adopt innovative construction practices, invest in digital workforce development, and align with Net-Zero 2045 and the SDGs. This study contributes a comprehensive policy-technology-investment roadmap for sustainable capital development in emerging economies.